The Effectiveness Of The Role Of The United Nations General Assembly In Addressing International Terrorism - ادلبي, منى; الدباس, مايا; سعد الدين, فراس (Latakia University Journal - Economic and Legal Sciences Series, 2021)
During the last decades of the twentieth century, the member states of the United Nations moved forward in their work in the field of combating international terrorism by using all the powers, authorities and organs of the United Nations to confront this phenomenon, especially the General Assembly as the general organ whose membership includes all the member states of the United Nations The United Nations was on both the legal and executive tracks, as it reached, through its efforts, the adoption of several resolutions dealing with the phenomenon of international terrorism. Despite the large number of resolutions issued by the United Nations General Assembly, it has been characterized by its limited role in combating the phenomenon of international terrorism, and perhaps this is due to its being affected in one way or another by the political conditions that the international community is going through on the one hand, in addition to the fact that it is not binding on states on the other hand, Until the late eighties, its decisions included all forms of terrorism, and explicitly included the need to distinguish between terrorism and the right of legitimate resistance, and condemned all forms of acts of terrorism, including those involving states, but the development of international events and the demise of the Soviet Union made it change its position under the influence and pressure of states. The resolutions of the General Assembly did not include official state practices or what is called state terrorism, but were limited to violence practiced by organizations with the support of states, and were absent from a reference to the rights of peoples to self-determination and their resistance to occupation by all available means. In this context, the researcher aimed to demonstrate the effectiveness of the role of the General Assembly in confronting the phenomenon of international terrorism, by presenting its resolutions related to terrorism, in order to present the developments and stages that those resolutions have gone through in addressing this phenomenon, and to reach results that help to understand that role. To present some points that would activate it in a way that helps to control and eliminate this phenomenon.